Introduction to Special Issue on comparative criminology: Context, scope and applicability in critical criminological research. (November 2022) - Light, Matthew; Singh, Anne-Marie
This Special Issue highlights the value of the comparative case study method for theory-building and refinement in criminology. Early figures in criminology, including those in the Chicago School, were aware of the importance of scope and applicability, which refer to the temporal, geographic, or other contextual boundaries of a theory, yet the field as a whole has not always given these issues due attention. While the discipline already deploys comparisons, the contributions in our collection showcase how a more structured and deliberate use of a comparative case study approach engages issues of context, scope and applicability of criminological theory including recent discussions about Anglocentrism and the Global North/South divide.